Analysis Of Coupling Efficiency On Fiber Lenses By Method Of Lines - Lambak, Zainuddin (2009)
In this thesis, the main objective is to develop the MOL methodology for analyzing the field propagation between the LD and SMF, in which four types of fiber lenses, i.e. hemispherical, hyperbolic, conical and asymmetrical taper lenses, were used in the cuoling technique.